Analisis Kontribusi dan Efektivitas Pajak Daerah Sebagai Sumber Pendapatan Aali Daerah Kabupaten Karawang - Suhono Suhono; Eva Maria Sulastri (UNSIKA (Universitas Singaperbangsa Karawang), 2017)
Local taxes are the source of local revenue. The collected local taxes can be used to support the economic growth of a region. The objectives of this research is (1) to identify the contribution of each post of local taxes to the locally-generated revenue of Kabupaten Karawang in 2011 – 2015 and (2) to identify the effectiveness of each local tax in Kabupaten Karawang to the locally-generated revenue in 2011 – 2015.This research used the quantitative method, which is the ratio analysis. Ratio analysis used is the contribution ratio and effectiveness ratio. Data used in this research is secondary data obtained from Dinas Pendapatan dan Pengelolaan Keuangan Kabupaten Karawang in 2011 – 2015. The result of this research shows that the contribution of each post of the local taxes to the locally-generated revenue of Kabupaten Karawang is in the low category with the percentage of 1% to 20%. The effectiveness for each local tax in Kabupaten Karawang is in the very effective category with the average effectiveness ratio of higher than 100%.